Pap smear uptake and its associated factors among Orang Asli women in Selangor - Abdul Manaf, Rosliza; Ismail, Suriani; Indra, Iis Sulastri; Mahamud, Mohamad Zahari; Ng, Zhi Ling (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Pap smear screening may increase the quality of women’s health through early detection of cervical cancer thus providing a better prognosis for women with cervical cancer. While the benefit of Pap smear screening is well documented, the screening uptake among Malaysian women in general was unsatisfactory with only 47.3% being screened. This study aimed to determine the prevalence of Pap smear uptake and its associated factors among Orang Asli women who lives in rural areas in Selangor. Methods: A cross sectional study was conducted in Hulu Langat and Kuala Langat districts from April to July 2017. Through cluster sampling, five Orang Asli settlements in the two districts were chosen. All women in the selected village aged between 18 to 65 years were invited to participate and interviewed using a structured, pretested questionnaire. Data were analysed using SPSS Version 22. Univariate and bivariate analysis were conducted to identify factors associated with Pap smear uptake among the participants. All hypotheses tests were two-sided and level of significance was set at 0.05. Results: Out of the 147 respondents, 114 (77.6%) had undergone Pap smear for at least once in the past. Women aged more than 35 years (p=0.013) were shown to be significantly more likely to take Pap smear compared to women who were 35 years old and less. There were significant associations between marital status (p<0.001), knowledge (p<0.001), attitude (p<0.001) and use of oral contraceptive (p=0.001) with Pap smear uptake. Conclusion: This study showed a high prevalence of Pap smear uptake among Orang Asli women in Selangor.